Liver disease in mitochondrial disorders. - Lee, W.S.; Sokol, R.J. (2007)
Liver involvement, a common feature in childhood mitochondrial hepatopathies, particularly in the neonatal period, may manifest as neonatal acute liver failure, hepatic steatohepatitis, cholestasis, or cirrhosis with chronic liver failure of insidious onset. There are usually significant neuromuscular symptoms, multisystem involvement, and lactic acidemia. The liver disease is usually progressive and eventually fatal. Current medical therapy of mitochondrial hepatopathies is largely ineffective, and the prognosis is usually poor. The role of liver transplantation in patients with liver failure remains poorly defined because of the systemic nature of the disease that does not respond to transplantation. Several specific molecular defects (mutations in nuclear genes such as SCO1, BCS1L, POLG, DGUOK, and MPV17 and deletion or rearrangement of mitochondrial DNA) have been identified in recent years. Prospective, longitudinal multicenter studies will be needed to address the gaps in our knowledge in these rare liver diseases.